Schädigungsverhalten von in CFK-Laminaten eingebetteten Inserts unter bauteilnahen Beanspruchungen - Pottmeyer, Florentin (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
Mechanical fasteners, so-called insert, offer the opportunity to allow for an inexpensive, detachable connection of thin-walled carbon fiber reinforced plastics (CFRP) parts to metal- or other plastic-based structures in the context of multi-material design. The present work is comprised of a systematic comparison of both insert types under near-application load conditions, whereby the strength as well as the damage behavior were evaluated.